The role of adenosine monophosphate-activated protein kinase and serum amyloid A proteins in the early diagnosis of neonatal sepsis - P.A. Orujova; N.H. Sultanova (Сучасна педіатрія: Україна)
Neonatal sepsis is a leading cause of mortality among newborns globally, with an incidence of 1 per 1,000 live births. Current diagnostic markers such as C-reactive protein (CRP) and procalcitonin (PCT) lack specificity and sensitivity for early diagnosis, highlighting the need for more reliable biomarkers.